The symmetry of children's knees is linked to their adult sprinting speed and their willingness to sprint in a long-term Jamaican study. - Robert Trivers (Public Library of Science (PLoS), 2013)
Jamaican athletes are prominent in sprint running but the reasons for their success are not clear. Here we consider the possibility that symmetry, particularly symmetry of the legs, in Jamaican children is linked to high sprinting speed in adults. Our study population was a cohort of 288 rural children, mean age 8.2 (± 1 SD = 1.7) years in 1996. Symmetry was measured in 1996 and 2006 from the fluctuating asymmetry (FA) of three lower-body traits and we constructed a lower body composite FA trait (Comp lb-FA). In 2010 we measured sprinting speed (for 90 m and 180 m races) in participants recruited from our original cohort. There were 163 untrained adults in our sample. We found: (i) high Comp lb and knee symmetry in 1996 and 2006 were linked to fast sprinting times in our 2010 runners and (ii) our sample of sprinters appears to have self-selected for greater symmetry. We conclude that high knee symmetry in childhood is linked to an ability to sprint fast in adult Jamaicans as well as a readiness to sprint.